(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
A Central Industrial Finance corporation was set up underthe Industrial Finance Corporations Act, 1948 in order to provide medium andlong term credit to industrial undertakings which fall outside normalactivities of commercial banks. The State governments expressed their desirethat similar corporations be set up in States to supplement the work of the IndustrialFinancial Corporation. State governments also expressed that the StateCorporations be established under a special statue in order to makeit possible to incorporate in the constitutions necessary provisions inregard to majority control by the government, guaranteed by the Stategovernment in regard to the payment principal. In order to implement the viewsexpressed by the State governments the State Financial Corporation bill wasintroduced in the Parliament.